History of Islamic Civilization in the Ayyubiyah Dynasty (1171-1250 AD) - Mizan, Khairul; Hajar, Ibnu; Fawzani, Nurul; Mubaraq, Zulfi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Islamic civilization during the Ayyubid dynasty is very important to study, especially the development of Sunni because Sunni is a form of school that became Shalahuddin's first policy to replace Shia at that time. This paper aims to discuss concrete forms of Sunni development during the Ayyubid dynasty, factors of Sunni development, and the impacts of its development. The type of research used was library research, the data were obtained from previous literature so that data collection technique used was documentation. This study found, first, the form of Sunni development began with the change of schools of thought from Shia to Sunni, the incessant development of madrasas, the prohibition on using books left by the Fatimids and the elimination of the sentence Hayya Ála Khairi Amal at the call to prayer; second, Sunni development was caused by internal factors such as the founding of the Ayyubid dynasty and Shalahuddin's Sunni background. Apart from these factors, Sunni development was also caused by external factors, namely, the majority of the world's Muslims are Sunnis and the dualism of the Shiites in Egypt; and third, the impact of Sunni developments on education, in which many madrassas were built and the reactivation of the Azhar mosque into a Sunni-based university.